Communication for Social Change: Seldom a Stand Alone, and Rarely Verified - Ricardo Ramirez; Wendy Quarry (The Evaluation Center at Western Michigan University, 2019)
Background: Communication for social change is rarely a stand-alone initiative. More often it is combined with several communication purposes such as networking, organizational visibility, information dissemination, or behavioural change.   Purpose: This article reports on an inter-disciplinary, capacity building experiment that combines communication strategy development with Utilization-Focused Evaluation (UFE).   Setting: The analysis stems from close to a dozen case studies where we tested a hybrid approach of UFE and communication strategy development. Our partners were research teams in a variety of areas including open education, open and collaborative science, Internet privacy, cyber-security, and open data. The Networked Economies Program of the International Development Research Centre (IDRC, Ottawa) funded each one of the research teams. The partners were based in different countries and had a global reach.   Intervention: The authors are members of a research project entitled "Designing Evaluation and Communication for Impact" (DECI) that provides mentoring in evaluation and communication to partners. This article focuses mainly on lessons from DECI-2, the second phase of the project that was operational from 2012-2017. DECI is led by a team in Canada and has engaged regional mentors based in Latin America, Asia and East Africa, who have provided much of the capacity building support to partners in their regions. At the end of each mentoring cycle, the DECI team produced a case study summarizing the experience. The collection of these case studies is the basis for this article.   Research Design: This article is a meta-evaluation of the experiences gained from the mentoring. It brings the findings from the grounded work and seeks to find theoretical insights from the evaluation and communication literature. Existing family trees in evaluation and communication are reviewed in search for commonalities that underlie the hybrid decision-making framework.   Data Collection and Analysis: The article leans on the findings of the case studies and the hybrid framework. Our analysis builds on earlier work by the authors in communication for social change. In particular, we analyze a common pattern where communication strategies tend to encompass several purposes in tandem. We refer to the planning steps in utilization-focused evaluation as a structured decision-making process that can help organize communication planning. Finally, we reflect on the benefits of formulating communication objectives that can be tracked or measured.   Findings: The hybrid decision-making framework allows communication planners to add some rigor to their strategies. At the same time, it invites evaluators to introduce evaluation questions about the outcomes of a communication intervention. An external evaluation of the DECI-2 project concluded that the combined decision-making process enabled partners to become better at adaptive management. The process introduced reflection spaces and helped teams adjust their projects as research findings emerged, and as conditions shifted in the policy arenas that they sought to influence.